Validation of clonal line females for sex determination studies in nile tilapia Oreochromis niloticus L. (Research in Agriculture Livestock and Fisheries, 2015)
Sex determination in the Nile tilapia Oreochromis niloticus is more complex than a simple XX-XY sex determining mechanism, as evidenced from fairly frequent unexpected sex ratios in progeny. The production of uniform, homozygous experimental material is particularly advantageous for studying sex determining mechanism as well as for the genetic mapping and genome sequencing studies in which interpretations are facilitated by homozygosity. To better understand the genetic mechanism of sex determination, a fully inbred line of clonal females (XX) was verified in controlled environmental conditions using test crosses and microsatellite DNA markers from the tilapia linkage map. A total of successfully amplified 87 microsatellite DNA markers covering all 24 linkage groups were selected for screening sexually mature females from this line. 67 markers were found polymorphic in outbred individuals screened. Markers from LG1, LG3 and LG23 were given more emphasis because sex determining genes have been mapped on these LGs in different species of tilapia. The verification and validation of this clonal line of females made them an important resource to use as a standard reference line in genomics, sex determination studies and other studies in Nile tilapia. DOI: http://dx.doi.org/10.3329/ralf.v1i1.22378 Res. Agric., Livest. Fish.1(1): 147-158, Dec 2014